(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
Our study aiming to define the term ‘swimming ability’ is based on international literature and examines the competency-based school swimming education system, taking into consideration the blueprints and paradigms of our times. We are comparing public-school instructions, schemes and the curriculum of elementary and civic schools to our previously collected data processed with the help of historical analysis extending from 1918 to 2020. The classification of the analysed documents is based on how much data they specifically store about water safety and swimming competencies. As a result, we are going to showcase the curriculums that were built mostly around the mentioned competencies and the direction in which the swimming education is developing in Hungary.